Crecimiento de la mazorca de tres clones de cacao (Theobroma cacao L.) y su relación con la incidencia de la monilla (Moniliophthora roreri E.) - Tigmasa Burgos, Paola Manuela (2017)
The following research project was carried out at the Experimental Farm "La Represa" belonging to the Quevedo State Technical University located at kilometer 7.5 in the Fayta site, on the Quevedo - San Carlos road. In order to determine the relationship between the incidence of monillia and cob growth in three cocoa clones (EET-103, CCN-51 and JHVH- 10) between the months of March and August of 2017. of a Completely Random Design, having in study three treatments (clones) and six repetitions (cobs). During the six months of the investigation the following variables were evaluated: total weight of the cob, weight of the shell, fresh weight of almond, diseased ears, healthy ears, total ears, number of almonds, total almonds and finally incidence of monillia. Data were collected from the ears every week and finished with the harvest, followed by analysis of the variables under study. The results indicated that the CCN-51 clone had the lowest incidence of monillia, and with the clone JHVH-10 had the largest cob size, the EET-103 clone recorded the highest number of ears both diseased and healthy but their size was lower than the CCN-51 and JHVH-10 clones. According to the analysis performed, according to the results of the analyzes it was determined that the ears are mostly affected by the disease during the second month and therefore cultural management must be carried out to avoid the spread of the infection.